REFORMING IN THE SPHERE OF HOUSING AND UTILITIES IS THE MOST IMPORTANT STATE PROGRAM - Tаlipova Nargiza Zukhritdinovna; Omonova Dilnoza Fayziddinovna; Kadabayeva Shahnoza Saidjanovna; Ahadullayeva Sarvinoz Komil qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides an analysis of the current state of housing and communal services, development programs for this industry. The problems of successful development of housing and communal services are identified, the main directions for improving the management of the development of housing and communal services are outlined. And also given information about the goals of reforming the housing and communal services.